2005
DOI: 10.1111/j.1365-2648.2005.03507.x
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making tree for women considering hysterectomy

Abstract: Nurses working in gynaecological services should understand how women decide to undergo hysterectomy so that the proper counselling and follow-up can be provided. With further testing, our decision tree may help in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For each decision tree, possible outcomes are assigned a numerical value and the probability of reaching an outcome is assessed. Wu et al. (2005) used a decision tree model to assess how women decide on whether to have a hysterectomy.…”
Section: The Information‐processing Modelmentioning
confidence: 99%
“…For each decision tree, possible outcomes are assigned a numerical value and the probability of reaching an outcome is assessed. Wu et al. (2005) used a decision tree model to assess how women decide on whether to have a hysterectomy.…”
Section: The Information‐processing Modelmentioning
confidence: 99%
“…, Wu et al . ). Patients desire information about topics such as treatment options, risks, prognosis and the progress and duration of treatment (Suhonen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, our findings are consistent with a report that concluded that once a woman has decided that her health is her most important need, she becomes more able to discard the idea of the uterus as a totem of womanhood (Wu et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This surgical procedure is conducted mainly to improve the quality of life of women, and generally as a way to prevent cervical cancer. A number of studies have indeed confirmed that hysterectomies do relieve women of painful symptoms and contribute to an improved quality of life (Williams and Clarke, 2000;Wu et al, 2005). In her study of African American's experiences of hysterectomy, Augustus (2002:299) found that even though ''women expressed that the operation was done at great emotional cost'', they nevertheless acknowledged experiencing benefits that included ''relief from pain and personal embarrassment and enhanced sexuality''.…”
Section: Benefits Of a Hysterectomymentioning
confidence: 93%